Diversity and Evolution of Butterfly Wing Patterns An Integrative Approach - Sekimura, Toshio; Nijhout, H. Frederik (Springer Singapore : Imprint: Springer, 2017)
This book facilitates an integrative understanding of the development, genetics and evolution of butterfly wing patterns. To develop a deep and realistic understanding of the diversity and evolution of butterfly wing patterns, it is essential and necessary to approach the problem from various kinds of key research fields such as “evo-devo,” “eco-devo,” ”developmental genetics,” “ecology and adaptation,” “food plants,” and “theoretical modeling.” The past decade-and-a-half has seen a veritable revolution in our understanding of the development, genetics and evolution of butterfly wing patterns. In addition, studies of how environmental and climatic factors affect the expression of color patterns has led to increasingly deeper understanding of the pervasiveness and underlying mechanisms of phenotypic plasticity. In recognition of the great progress in research on the biology, an international meeting titled “Integrative Approach to Understanding the Diversity of B utterfly Wing Patterns (IABP-2016)” was held at Chubu University, Japan in August 2016. This book consists of selected contributions from the meeting. Authors include main active researchers of new findings of corresponding genes as well as world leaders in both experimental and theoretical approaches to wing color patterns. The book provides excellent case studies for graduate and undergraduate classes in evolution, genetics/genomics, developmental biology, ecology, biochemistry, and also theoretical biology, opening the door to a new era in the integrative approach to the analysis of biological problems.  This book is open access under a CC BY 4.0 license. .